Approximations of Entire Functions in Locally Global Norms - S.K. Jassim; N.J. Mohamed (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
The purpose of this paper is to evaluate the error of the approximation of an entire function by some discrete operators in locally global quasi-norms (Ld,p-space), we intend to establish new theorems concerning that Jackson polynomial and Valee-Poussin operator remain within the same bounds as bounded and periodic entire function in locally global norms (Ld,p), (0 < p Â£ 1).